Impact of Allopurinol Pretreatment on Coronary Blood Flow and Revascularization Outcomes after Percutaneous Coronary Intervention in Acute STEMI Patients: A Randomized Double Blind Clinical Trial - Mohammad Kermani-Alghoraishi, MD; Hamid Sanei; Kiyan Heshmat-Ghahdarijani; Rahil Ghahramani; Mehrdad Honarvar; Masoumeh Sadeghi (ARYA Atherosclerosis, 2023)
INTRODUCTION: The generation of reactive oxygen species, which is induced by the activation of the xanthine oxidase (XO) enzymatic system, is one of the primary causes of ischemia-reperfusion injury for an ischemic heart. Allopurinol, as an XO inhibitor, plays an inhibitory role in free radical production in ST-elevation myocardial infarction (STEMI) patients. The aim of this study is to evaluate the impact of allopurinol pre-treatment on post-revascularization outcomes in patients admitted with STEMIMETHOD: Ninety patients with acute STEMI were enrolled in this randomized double-blind clinical trial and divided into two equal groups. The allopurinol group received a 600 mg allopurinol loading dose before the emergency PCI, and the control group received a placebo medication of the same shape. Thrombolysis in Myocardial Infarction (TIMI) flow, ECG changes, troponin level, and the occurrence of major cardiac events (MACE) during a 1-month follow-up were assessed.RESULTS: In the end, 81 patients were analyzed. The mean age of the patients was 59.52(11.31) and 61.3(9.25) in the allopurinol and control groups, respectively (p = 0.49). The troponin level 48 hours after the PCI and ST-elevation regression showed no significant difference between the groups [(p = 0.25) and (p = 0.21), respectively]. TIMI flow had improved in the allopurinol group compared to the placebo (p = 0.02). The PCI success rate was 78.6% and 61.5% in the case and control groups, respectively (p = 0.09). MACE and other clinical outcomes were similar between the groups (p > 0.05).CONCLUSION: This study revealed that allopurinol pre-treatment could improve TIMI flow in patients undergoing primary or rescue PCI in an acute STEMI setting.